Ethical and Privacy Analysis in the Use of Generative AI in the World of Education - Harahap, Henrawansyah; Sofyan, Muhammad (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2025)
This research aims to critically analyze the ethical and privacy aspects in the use of generative AI in the world of education. The research method used is a qualitative approach with literature studies, analyzing various academic literature, educational policies, and regulations related to data protection and technological ethics. The results show that while generative AI provides great benefits such as personalized learning, automated content creation, and increased efficiency, it also poses risks in the form of academic cheating, privacy violations, and decreased critical thinking skills. In the context of Islamic Religious Education, AI must be utilized responsibly by integrating Islamic ethical values such as honesty, fairness, and respect for privacy. This study concludes that the ethical implementation of generative AI requires a strong regulatory framework, teacher competency enhancement, and awareness of the importance of privacy protection in order for AI integration to make a positive contribution to education.